A spray technique for mass release of eggs of Micromus tasmaniae Walker (neuroptera: Hemerobiidae) - Hussein, Mohd Yusof (Elsevier, 1984)
Laboratory and glasshouse tests showed that eggs of Micromus tasmaniae Walker (Neuroptera: Hemerobiidae) can be sprayed at 206 kPa pressure with a specially developed compressed-air sprayer without impairing viability. The effects of five materials (agar, sucrose, gelatin, plant glue and xanthan gum) in water solution on egg hatching were tested and xanthan gum solution (0·03%) was selected as a suitable liquid medium for suspending the eggs and making them adhere to potato foliage. Egg losses during spraying may be greatly affected by wind drift, the amount of exposed soil (which is related to the stage of foliage development) and other environmental factors. The possibility of a spray technique for mass release of M. tasmaniae eggs in the biological control programme for potato pests is discussed.